Antiretroviral Therapy in Severely Malnourished, HIV-infected Children in Asia - Boettiger D. (2017)
© Copyright 2016 Wolters Kluwer Health, Inc. All rights reserved. Background: Information on antiretroviral therapy (ART) use in HIV-infected children with severe malnutrition (SM) is lacking. We investigated long-term ART outcomes in this population. Methods: Children enrolled in the TREAT Asia Pediatric HIV Observational Database who had SM (weight-for-height or body mass index-for-age Z score less than -3) at ART initiation were analyzed. Generalized estimating equations were used to investigate poor weight recovery (weight-for-age Z score less than -3) and poor CD4% recovery (CD4% < 25), and competing risk regression was used to analyze mortality and toxicity-associated treatment modification. Results: Three hundred fifty-five (11.9%) of 2993 children starting ART had SM. Their median weight-for-age Z score increased from -5.6 at ART initiation to -2.3 after 36 months. Not using trimethoprim-sulfamethoxazole prophylaxis at baseline was associated with poor weight recovery [odds ratio: 2.49 vs. using; 95% confidence interval (CI): 1.66-3.74; P < 0.001]. Median CD4% increased from 3.0 at ART initiation to 27.2 after 36 months, and 56 (15.3%) children died during follow-up. More profound SM was associated with poor CD4% recovery (odds ratio: 1.78 for Z score less than -4.5 vs. -3.5 to less than -3.0; 95% CI: 1.08-2.92; P = 0.023) and mortality (hazard ratio: 2.57 for Z score less than -4.5 vs. -3.5 to less than -3.0; 95% CI: 1.24-5.33; P = 0.011). Twenty-two toxicity-associated ART modifications occurred at a rate of 2.4 per 100 patient-years, and rates did not differ by malnutrition severity. Conclusion: Trimethoprim-sulfamethoxazole prophylaxis is important for the recovery of weight-for-age in severely malnourished children starting ART. The extent of SM does not impede weight-for-age recovery or antiretroviral tolerability, but CD4% response is compromised in children with a very low weight-for-height/body mass index-for-age Z score, which may contribute to their high rate of mortality.